Development of Labyrinth Media to Stimulate Prosocial Behavior Skills of 5-6 years old Children in Purwakarta - Alsafiah, Cut Mutia; Tabroni, Imam; Mark, Elladdadi; Maharjan, Kailie (Journal of Computer Science Advancements, 2023)
This study aims to produce a valid labyrinth learning media to improve the ability of prosocial behavior in children aged 5-6 years. This research is a development research with the development model used by Sugiyono. In this study, researchers only used 7 (seven) stages, namely knowing problems and potential, data collection, product design, design validation, design revision, product trials and product manufacturing. The next stage was not carried out due to cost and time constraints. The data collection technique used is a questionnaire, where the questionnaire is validated by material experts, media experts and educators. The type of data generated is quantitative and qualitative data. The average percentage result of the pretest conducted on 3 children is 10.6%, proving that the child’s condition is still in the undeveloped stage. Then the posttest was carried out, namely the condition after the child was given the labyrinth media, the average percentage result of this posttest was 14.6% which proved that the child experienced a change in condition to develop as expected. So it can be concluded that the Labyrinth media to improve the ability of prosocial behavior of children aged 5-6 years has met the criteria for validity.